Beverly, Right Here - DiCamillo, Kate (Somerville, Massachusetts : Candlewick Press, 2019)
"Beverly Tapinski has run away from home plenty of times, but that was when she was just a kid. By now, she figures, it's not running away. It's leaving. Determined to make it on her own, Beverly finds a job and a place to live and tries to forget about her dog, Buddy, now buried underneath the orange trees back home; her friend Raymie, whom she left without a word; and her mom, Rhonda, who has never cared about anyone but herself. Beverly doesn't want to depend on anyone, and she definitely doesn't want anyone to depend on her. But despite her best efforts, she can't help forming connections with the people around her--and gradually, she learns to see herself through their eyes." --Provided by the publisher
Junior Library Guild
Ages 10-12.
Grades 5-7.
480
A Junior Library Guild selection
Keywords: Dysfunctional families -- Juvenile fiction; Friendship -- Juvenile fiction; Runaway teenagers -- Juvenile fiction; Self-actualization (Psychology) -- Juvenile fiction; Family problems -- Fiction; Friendship -- Fiction; Runaways -- Fiction; Self-actualization (Psychology) -- Fiction; Family life -- Fiction; Friendship -- Fiction; Runaway teenagers -- Fiction; Self-realization -- Fiction